Sodium selenite enhanced the selenium content in black soldier fly - Yifan Li; Han Chen; Yunting Zhang; Shoukang Cao; Huihui Wang; Zhentao Lu; Xuezhuang Wu (Scientific Reports)
Abstract This study focuses on the effects of different levels of sodium selenite on the growth, selenium content, and antioxidant capacity of black soldier fly (Hermetia illucens). The experiment used different doses of sodium selenite for treatment, including a basic diet with no supplements (control) and diets supplemented with 10 mg/kg (Se10), 20 mg/kg (Se20), 30 mg/kg (Se30), and 40 mg/kg (Se40) sodium selenite, and results show that sodium selenite supplementation significantly increases selenium content and improves selenium utilization and antioxidant capacity (P < 0.05). However, it also negatively affects growth performance and the utilization of other nutrients. The optimal level of sodium selenite supplementation depends on the ration of selenium enrichment with the overall health and productivity of black soldier fly.